Desempenho agronômico e teor de clorofila na relação com a absorção de água em alface - Santos, Camila Peixoto dos (2020)
Lettuce (Lactuca sativa L.) is the main leafy vegetable, with the curly type with light green leaves the preferred in Brazil. However, leaves of intense green color (higher chlorophyll content) have increased consumer preference. Thus, to evaluate agronomic characteristics of lettuce lines with more intense staining and their efficiency in water use is important. This study aimed to correlate mass production and water consumption by evaluating lettuce lines and varieties with different chlorophyll contents. The experiment was conducted in two stages: in the hydroponic system (1st stage) and in Chamber B.O.D. (2nd stage). Ten lettuce lines and two varieties (Vanda and Luiza) were evaluated for agronomic characteristics and chlorophyll contents in the leaves, in a randomized block design with four replications (1st stage). The evaluation phase of productivity and chlorophyll contents in hydroponic system allowed the selection of four lines and two varieties with different chlorophyll contents and which were used for experiments in B.O.D. chamber to evaluate the mass gain and its correlation with water absorption. The highest chlorophyll contents were found for Luiza (43.31) and sline 09 (39.50), intermediate values for 27 and 47 and lower for 195 and Vanda. In the experiments carried out in B.O.D. the sline 195 and the varieties Vanda and Luiza showed the highest mass gains with approximately 0.07 g plant-1, as well as the highest water consumption, with 54 ml plant-1. The strain 47 and Luiza presented the highest number and stomata per cm², approaching 18,000 units. Luiza showed better efficiency in water use, consuming approximately 750 ml to produce one gram of dry mass. The water consumption by the plants was not influenced by chlorophyll content, but showed a positive correlation with the production of final fresh mass, final dry mass and consequently with the mass gain of lettuce plants. Genotypes with higher chlorophyll content showed lower mass production. Thus, from this work it was possible to conclude that genotypes with higher chlorophyll content have lower capacity in terms of mass production.